2008
DOI: 10.2165/00044011-200828020-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Fixed Combination of Cinnarizine/Dimenhydrinate for the Treatment of Patients with Acute Vertigo Due to Vestibular Disorders

Abstract: The fixed combination of cinnarizine/dimenhydrinate was shown to be an effective and very well tolerated treatment option for patients with acute vertigo due to vestibular disorders. The combination proved to be significantly more efficient in reducing vertigo and associated vegetative symptoms than betahistine in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
1
12
0
2
Order By: Relevance
“…The findings of the present study are largely in line with results from previously conducted randomized, double-blind controlled clinical trials, where the fixed-combination preparation has been shown to be significantly more effective than betahistine (dimesylate) in patients with otogenic vertigo [21], vertigo due to vertebrobasilar insufficiency [23], acute vestibular disorders [24], or vestibular neuritis [26], and non-inferior in patients with Menière’s disease [27, 28], respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of the present study are largely in line with results from previously conducted randomized, double-blind controlled clinical trials, where the fixed-combination preparation has been shown to be significantly more effective than betahistine (dimesylate) in patients with otogenic vertigo [21], vertigo due to vertebrobasilar insufficiency [23], acute vestibular disorders [24], or vestibular neuritis [26], and non-inferior in patients with Menière’s disease [27, 28], respectively.…”
Section: Discussionsupporting
confidence: 88%
“…There is insufficient evidence demonstrating the relative efficacy of any given class over another. 205-207…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…For instance, there is a study in which one Group of patients was given low-dose betahistine (12 mg) and the other Group was given a combination of cinnarizine (20 mg) and dimenhydrinate (40 mg) three times a day. The patients were assessed clinically [25,26] and the combination of dimenhydrinate and cinnarizine, compared to betahistine, provided better control of acute vertigo treatment and vegetative symptoms. Dimenhydrinate and cinnarizine, which is a vestibulosuppressant combination, had better control of episodes of vertigo in this study.…”
Section: Groupmentioning
confidence: 99%